Adolescent development of insula‐dependent interoceptive regulation. Issue 5 (19th June 2016) - Li, Dawei; Zucker, Nancy L.; Kragel, Philip A.; Covington, Virginia E.; LaBar, Kevin S.
Abstract: Adolescence is hypothesized to be a critical period for the maturation of self‐regulatory capacities, including those that depend on interoceptive sensitivity, but the neural basis of interoceptive regulation in adolescence is unknown. We used functional magnetic resonance imaging and psychophysiology to study interoceptive regulation in healthy adolescent females. Participants regulated their gut activities in response to a virtual roller coaster by deep breathing aided by visually monitoring their online electrogastrogram (EGG) activity through a virtual thermometer (i.e. gut biofeedback), or without biofeedback. Analyses focused on the insula, given its putative role in interoception. The bilateral posterior insula showed increased activation in the no‐biofeedback compared to biofeedback condition, suggesting that the participants relied more on interoceptive input when exteroceptive feedback was unavailable. The bilateral dorsal anterior insula showed activation linearly associated with age during both induction and regulation, and its activation during regulation correlated positively with change of EGG in the tachygastria frequency band from induction to regulation. Induction‐related activation in the bilateral ventral anterior insula was nonlinearly associated with age and peaked at mid‐adolescence. These results implicate different developmental trajectories of distinct sub‐regions of the insula in interoceptive processes, with implications for competing neurobiological theories of female adolescent development. Abstract : This study investigated the brain mechanisms by which adolescents regulate their gut feelings in response to a virtual roller coaster ride. Participants were trained to use deep breathing exercises and biofeedback signals from their stomach (EGG) while brain activity was recorded using functional neuroimaging. Older adolescents show an increased reliance on a region of the insula, a brain area implicated in monitoring the body, to successfully regulate their gut activity.